2021
DOI: 10.2147/hiv.s328269
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Parasitosis and its Association with CD4+ T Cell Count and Viral Load among People Living with HIV in Parasite Endemic Settings of Northwest Ethiopia

Abstract: Purpose To study intestinal parasitosis and its association with viral load and CD4+ T cell count in HIV-infected individuals at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia. Methods A cross-sectional study was conducted from March to June 2019. Three hundred and sixteen study participants were selected using systematic random sampling technique. Sociodemographic and clinical data were collected using structured questionnaire. Stool sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The overall prevalence of gastrointestinal parasites in the present study was 24.2%. This prevalence is close to that obtained by [17] in Cameroon 27.9%, [25] Ghana (25.2%), [26] Brazil (28.88%), [15] Ethiopia (24.7%), and [14] Colombia (29.2%). Nevertheless, it was lower than the 52.08% obtained by Taheu et al in Yaoundé, Cameroon [16].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The overall prevalence of gastrointestinal parasites in the present study was 24.2%. This prevalence is close to that obtained by [17] in Cameroon 27.9%, [25] Ghana (25.2%), [26] Brazil (28.88%), [15] Ethiopia (24.7%), and [14] Colombia (29.2%). Nevertheless, it was lower than the 52.08% obtained by Taheu et al in Yaoundé, Cameroon [16].…”
Section: Discussionsupporting
confidence: 85%
“…With the improvement in the care of People Living with HIV (PLHIV) in recent years worldwide, the introduction of Highly Active Antiretroviral Therapy (HAART) as the primary treatment for HIV has led to a reduction in the frequency of infections; including those caused by enteroparasites [13]. A study in Antioquia, Colombia, in a population of people living with HIV and AIDS (PLWHA) on ART showed a prevalence of 29.2% [14] and a similar study in Ethiopia showed a prevalence of 24.7% [15]. In some regions in Cameroon a high prevalence of gastrointestinal parasites has been registered; 52.08% in Yaoundé [16], 27.9% in Douala [17], and 59.5% in Dschang (West) [18].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with a viral load count between 20 and 1000 cps/ml were more likely to develop parasitic infections compared to those with undetectable viral load counts. This finding suggests that individuals with higher viral loads may have compromised immune systems, making them more susceptible to opportunistic infections, including intestinal parasites ( 23 , 29 ). Additionally, patients in WHO stage 4 of HIV/AIDS had a higher likelihood of being infected with parasitic infections compared to those in stage 1.…”
Section: Discussionmentioning
confidence: 99%
“…The higher rates of HIV/AIDS in urban areas due to factors such as increased mobility, higher population density, and greater access to healthcare services, and the global HIV/ AIDS epidemiology reported that young adults are often at higher risk of HIV infection due to behavioral factors, including engaging in risky sexual behaviors and substance abuse. Low educational attainment is often associated with limited health literacy, which can hinder individuals' ability to understand and adopt preventive measures against parasitic infections (18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%